Efektivitas Mediasi dalam Penyelesaian Sengketa Perdata di Era Digital: Pendekatan Empiris terhadap Sistem Peradilan Indonesia - Kossay, Methodius; Idris, Maulana Fahmi; Pratiwi, Putri; Suwardi (Universitas Sains dan Teknologi Komputer, 2024)
This study explores the effectiveness of digital mediation in resolving civil disputes within Indonesia’s judiciary system, particularly in the era of rapid technological advancement. The growing backlog of cases and the high costs of litigation have emphasized the need for more efficient and accessible dispute resolution methods. Digital mediation emerges as a promising alternative, leveraging technology to bridge geographical barriers and reduce procedural delays. The study aims to analyze the factors influencing the success of digital mediation and identify challenges that hinder its implementation. Using a qualitative approach, this research collected primary data through in-depth interviews with mediators, disputing parties, and judicial policymakers. Secondary data were gathered from official court reports and relevant literature. The analysis involved thematic coding and interpretation of data to uncover patterns and insights. Case studies from urban, semi-urban, and rural courts provided a comprehensive understanding of the varying success rates of digital mediation. The findings reveal that mediator training in technology significantly enhances the success rate of digital mediation, particularly in urban areas with better digital infrastructure. However, rural areas face challenges such as limited internet access and low digital literacy, which impede the effectiveness of the mediation process. The study also highlights the importance of integrating judicial systems with digital mediation platforms and revising regulatory frameworks to ensure consistent implementation. This research contributes to the theoretical understanding of digital mediation and offers practical implications for policymakers. It underscores the need for targeted training programs for mediators and investments in digital infrastructure to promote equitable access. The findings provide a roadmap for improving digital mediation practices and suggest further exploration of user experiences and longitudinal impacts. By addressing existing challenges, digital mediation can become a cornerstone of Indonesia’s civil dispute resolution in the digital age.